Proteomic analysis of Lactobacillus pentosus for the identification of potential markers involved in acid resistance and their influence on other probiotic features. (June 2018) - Pérez Montoro, Beatriz; Benomar, Nabil; Caballero Gómez, Natacha; Ennahar, Said; Horvatovich, Peter; Knapp, Charles W.; Gálvez, Antonio; Abriouel, Hikmate
Abstract: Acidity often prevents the undesirable microbial colonization both in fermented foods and under gastric conditions. Thus, the acid resistance of Lactobacillus pentosus strains used as starter cultures and/or probiotics requires further understanding. This was investigated by means of comparative proteomic approach using three strains representing the phenotypes: resistant (AP2-15), intermediate (AP2-18) and sensitive (LP-1) to acidic conditions. Proteomic analysis of constitutive phenotypes revealed that the intrinsic resistance of L. pentosus is associated with the over-production of three principal proteins: 2, 3-bisphosphoglycerate-dependent phosphoglycerate mutase 2 (PGAM-d), elongation factor G and 50S ribosomal protein L10, and additionally on ATP synthase subunit beta and chaperone protein DnaK; they are associated with metabolic pathways of proteins and carbohydrates, energy production and stress responses. Suggested protein biomarkers for acid resistance in L. pentosus include elongation factor G and PGAM-d, both being abundantly found in the constitutive proteome of the resistant phenotype under standard and acidic conditions. Furthermore, L. pentosus strains pre-exposed to acids displayed enhanced probiotic function such as auto-aggregation ability via surface proteins. We conclude that pre-exposure of probiotic L. pentosus strains to acid may strategically enhance their performance as starter cultures and probiotics. Highlights: Proteomic data reveal acid resistance mechanisms in Lactobacillus pentosus. Elongation factor G and PGAM-d detected as acid resistance biomarkers in L. pentosus. High auto-aggregation ability of Lactobacillus pentosus strains pre-exposed to acids.